Accumulation and spatial distribution of copper and nutrients in willow as affected by soil flooding: A synchrotron-based X-ray fluorescence study. (March 2019) - Cao, Yini; Ma, Chuanxin; Zhang, Jianfeng; Wang, Shufeng; White, Jason C.; Chen, Guangcai; Xing, Baoshan
Abstract: Copper (Cu) induced phytotoxicity has become a serious environmental problem as a consequence of significant metal release through anthropogenic activity. Understanding the spatial distribution of Cu in plants such as willow is essential to elucidate the mechanisms of metal accumulation and transport in woody plants, particularly as affected by variable environment conditions such as soil flooding. Using synchrotron-based X-ray fluorescence (μ-XRF) techniques, the spatial distribution of Cu and other nutrient elements were investigated in roots and stems of Salix ( S. ) integra exposed to 450 mg kg −1 Cu under non-flooded (NF)/flooding (F) conditions for 90 d. S. integra grown in the F condition exhibited significant higher tolerance index (TI, determined by the ratio of total biomass in Cu treatments to control) ( p  < 0.05) than that in the NF condition, indicating soil flooding alleviated Cu toxicity to willow plants. The μ-XRF revealed that Cu was preferentially located in the root cap and meristematic zone of the root tips. Under the NF condition, the Cu intensity in the root epidermis was more highly concentrated than that of the F condition, suggesting the soil flooding significantly inhibited Cu uptake by S. integra . The pattern of the Cu spatial distribution in the S. integra stem indicated that the F condition severely reduced Cu transport via the xylem vessels as a consequence of decreasing the transpiration rate of leaves. To our knowledge, this is the first study to report the in vivo Cu distribution in S. integra in a scenario of co-exposure to the Cu and the soil flooding over a long period. The finding that Cu uptake varies significantly with flooding condition is relevant to the development of strategies for plants to detoxify the metals and to maintain the nutrient homeostasis. Graphical abstract: Image 1 Highlights: This is the first report of in situ Cu distribution in Salix. integra grown in flooded soil. Cu was preferentially localized in root cap and meristematic zone of root tips. Flooding conditions severely inhibited Cu transport via the xylem vessels. Synchrotron XRF enabled accurate mapping of Cu spatial distribution in willows.